Safety Study of Single-Dose Intravenously Administered DOTA-Siglec-9 Peptide in Sprague Dawley Rats - Chrusciel P; Yatkin E; Li XG; Jaakkola UM; Knuuti J; Jalkanen S; Roivainen A (SAGE PUBLICATIONS INC, 2022)
The peptide-based radioactive compound [Ga-68]Ga-DOTA-Siglec-9 is a novel agent for imaging of inflammation with positron emission tomography. The drug target of [Ga-68]Ga-DOTA-Siglec-9 is vascular adhesion protein 1. Previous studies have obtained promising results with [Ga-68]Ga-DOTA-Siglec-9 in experimental animals. However, before taking this novel imaging agent into clinical trials, safety and toxicological studies need to be performed with the nonradioactive precursor compound DOTA-Siglec-9. This extended single-dose toxicity study was designed to provide information on the major toxic effects of DOTA-Siglec-9 and to indicate possible target organs after a single intravenous (iv) injection in rats. The study was performed using 60 adult Hsd: Sprague Dawley rats and included a control group and a treatment group to investigate the toxicity of DOTA-Siglec-9 solution at a final concentration of 0.2 mg/mL after a single iv injection of 582 mu g/kg. The maximum dose tested was 1,000-fold the clinical dose on a mg/kg basis as indicated in European Medicines Agency International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use guideline M3(R2). The planned human clinical dose is approximately 0.582 mu g of DOTA-Siglec-9 per kg of body mass. This study demonstrates that iv administration of DOTA-Siglec-9 at a dose of 582 mu g/kg was well tolerated in rats and did not produce toxicologically significant adverse effects.